1988
DOI: 10.1002/1097-0142(19880615)61:12<2439::aid-cncr2820611208>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Gallium 67 imaging in monitoring lymphoma response to treatment

Abstract: The value of gallium 67 (Ga) imaging in monitoring lymphoma response to treatment was assessed in 25 patients with Ga-avid tumors and compared to body computed tomography (CT), chest radiographs, and palpation of tumor infiltrated peripheral lymph nodes. Ga imaging was negative in 95% (20/21) of the patients who were clinically considered to be in remission and in whom treatment was stopped. The disease did not recur during a follow-up of 12 to 26 months in 15 patients. Six patients developed recurrence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
1
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(38 citation statements)
references
References 13 publications
2
32
1
3
Order By: Relevance
“…However, gallium-67 scintigraphy ( 67 Ga) remains the most widely used nuclear tracer for evaluating lymphoma. [6][7][8][9] Although the mechanism of uptake of 67 Ga by lymphoma cells is not understood fully, its accumulation appears to depend in part on the density of the transferrin receptor (CD71) on tumor cells and the acidic condition of tumor tissues associated with anaerobic metabolism. [7][8][9] The major limitations of 67 Ga include relatively low sensitivity and accuracy, particularly for abdominal and extranodal sites.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…However, gallium-67 scintigraphy ( 67 Ga) remains the most widely used nuclear tracer for evaluating lymphoma. [6][7][8][9] Although the mechanism of uptake of 67 Ga by lymphoma cells is not understood fully, its accumulation appears to depend in part on the density of the transferrin receptor (CD71) on tumor cells and the acidic condition of tumor tissues associated with anaerobic metabolism. [7][8][9] The major limitations of 67 Ga include relatively low sensitivity and accuracy, particularly for abdominal and extranodal sites.…”
supporting
confidence: 89%
“…In particular, it should be noted that the sensitivity of 67 Ga in FL and SMZL was low (33% and 31%, respectively). These results are concordant with the observation that the degree of 18 F-FDG or 67 Ga accumulation is associated with cell proliferation and histologic grade, 8,20,30 and they suggest that caution should be used in the staging of indolent lymphoma by 67 Ga. One of the striking results of the current study was that the sensitivity of 67 Ga in MCL and NK-nasal was extremely low, whereas 18 F-FDG-PET detected disease sites in these subtypes with high sensitivity, because these 2 subtypes are aggressive clinically and are resistant to conventional chemotherapy (combined cyclophosphamide, doxorubicin, vincristine, and prednisone). [31][32][33][34] There have been few studies on the sensitivity of 67 Ga in these subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there has not been a comprehensive study comparing FDG-PET and Ga-67 scintigraphy, previous studies with a limited number of patients have reported sensitivities ranging between 94% and 100% in the detection of disease sites in lymphoma for FDG-PET and between 85% and 90% for Ga-67 imaging. 7,8,15,26 Although the site sensitivity for Ga-67 in our study is lower than previous reports, the patient sensitivity is consistent with these prior studies. Neoplastic tissues utilize glycolysis to meet their energy needs because of limited oxidation of intracellular metabolites.…”
Section: Discussionsupporting
confidence: 91%